Community Empowerment Through the Mantra Coin Chest Program at the East Java Province Maritime and Fisheries Service (Cultivated Fisheries Sector)" - Aurelli Salsabila Ariestawati; Vidya Imanuari Pertiwi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The Coin Box Program is an initiative of the East Java Provincial Government in order to alleviate poverty through community empowerment in the aquaculture sector. This program focuses on increasing the capacity of productive poor communities through training, mentoring, and assistance with fisheries facilities and infrastructure. This study aims to analyze the effectiveness of the program using the ACTORS (Authority, Confidence and Competence, Trust, Opportunities, Responsibilities, Support) theory approach, which emphasizes granting authority, increasing self-confidence, and support for beneficiary communities. The research method used is descriptive qualitative with data collection through observation, in-depth interviews, and document studies. The results of the study show that this program has a positive impact on increasing skills, income, and community independence in the aquaculture sector. However, there are still challenges in implementation, such as low levels of digital literacy in marketing, limited access to land, and lack of regeneration of young workers. Therefore, more innovative strategies are needed, such as involving the younger generation, increasing the use of technology, and strengthening coordination between stakeholders. Overall, the Coin Box Program has proven effective in improving the welfare of productive poor communities and has the potential to become an empowerment model that can be applied in other areas. The sustainability of this program requires further support from the government and collaboration with various parties to optimize the results achieved.